Morphological analysis-based yield modeling in greenhouse grown cherry tomato (Solanum lycopersicum) under prolonged heat stress - Kim, Sumin; Jeong, Jaehak; Kim, Sojung (Frontiers in Plant Science, 2025)
In South Korea, cherry tomato (Solanum lycioersucum) is a major greenhouse vegetable crop. However, climate change has steadily raised Earth’s average temperature, posing a serious challenge for greenhouse agriculture. Elevated temperatures can trigger heat stress in greenhouse crops, leading to considerable yield losses. This study developed a greenhouse tomato growth model for two cherry tomato accessions, HR17 and HR24, cultivated under heat stress conditions during growing periods. Climate projections based on polynomial regression were incorporated into the plant growth model to assess climate change impacts on tomato yields. The two tomato accessions demonstrate distinct growth characteristics: HR24 allocates more biomass relative to fruit yield (Harvest index:0.48), whereas HR17 shows greater fruit production than biomass accumulation (Harvest index:0.65). Their yield responses also vary under future climate scenarios highlighted by temperature increases of 1-8°C and extended hot seasons compared to historical records. HR24 appears more resilient to heat stress than HR17. Under Climate Change scenarios (SSP245 and SSP585 pathways), HR17 will decrease its fruit yield by around 1.2 Dry Ma/ha, while HR24 yields will be increased by round 1.3 Dry Mg/ha. This increased tolerance in HR24 may be attributable to its ability to sustain photosynthetic activity through higher production of biomass organs such as leaves and stems. These findings form a foundation for developing greenhouse crop models in future research and supporting farmers by providing more reliable yield forecasts.